Peran Komunikasi Orang Tua terhadap Kesehatan Reproduksi pada Remaja - Ana Rizqy Soliha; Wahyu Agung Budi Alamsyah; Nur Mufida Wulan Sari; Mochammad Bagus Qomaruddin (Journal of Telenursing (JOTING), 2023)
This research aims to determine whether parental communication in adolescent reproductive health services plays a role in encouraging adolescents to utilize reproductive and sexual health services. This research method uses a literature review with a critical appraisal JBI (Joanna Briggs Institute). The search was carried out through the English and Indonesian PubMed, Science Direct, and PlosOne databases 2020-2022 using relevant keywords in different orders: â€œSexual Health,â€ â€œParents,â€ â€œFamily,â€ â€œHealth Services,â€ â€œReproductive Health,â€ Sexual Health and Reproduction.â€ The research results show that the influence of parents in encouraging access to reproductive health services is the lack of parental education, adequate family economics, living with parents, and the lack of facilities provided by the local government. In conclusion, teenagers rarely use sexual and reproductive health in health facilities because parents do not allow it based on culture, which creates lousy stigmatization when visiting health facilities. There is no financial support for teenagers to access reproductive health services in health facilities, so parents play a role in increasing or not increasing the utilization of sexual and reproductive health services by adolescents. Keywords: Family, Reproductive Health, Sexual Health